Coordination of hybrid vehicles strategies to improve fuel consumption and reduce the economic cost - Dawood, Basima Taresh; Ahmad, Yasser; Kadhim, Amjed Alwan (Institute of Advanced Engineering and Science, 2024)
To reduce fuel consumption and environmental pollution, this study focused on coordinating the use of a hybrid vehicle, that is, a bus type, powered by a diesel and electric engine. Solar cells have been added to the roof of the bus lighting, heating, and cooling, and fuzzy logic is applied to control the battery charge. Adding solar energy charge the battery by 25% of the total battery charge, thereby reducing fuel costs. The time was also calculated with the battery charge, and the battery is charge more. The aim of the research is to reduce environmental pollution and to use artificial intelligence to control the hybrid vehicle battery charge and speed.